The Influence of Youtube Media on Writing Short Story Texts in Class VI Students of SD Negeri 2 Percontohan Blangkejeren - Fitria Ratnawati; Sadieli Telaumbanua; Yenita Br. Sembiring (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The research entitled "The Influence of Using YouTube Media on the Short Story Text Writing Skills of Grade VI Students at SD Negeri 2 Percontohan Blangkejeren aims to determine the extent of the influence of using YouTube media on the ability to write short story texts for Grade VI students at SD Negeri 2 Percontohan Blangkejeren. Quantitative approach to experimental methods. An experimental design was used to test the effect of using YouTube media on students' ability to write short story texts. This research involved a control group and an experimental group to compare the results between students who used YouTube media in learning to write short stories with students who did not use this media. Data was collected through short story text writing tests before and after treatment using YouTube media. Data analysis was carried out using statistical methods to measure the influence of using YouTube media on students' short story writing skills. The results of the research show that the tcount of 26.207 is much greater than the ttable value of 1.76, so h0 is rejected and H1 is accepted so it can be concluded that the use of YouTube media in learning to write short stories has a positive influence on the writing ability of class VI students at SD Negeri 2 Percontohan Blangkejeren. Students who used YouTube media experienced a significant increase in writing skills with an average of 67.89 compared to students who did not use this media with an average of 42.31.